The Influence of Location and Gender on the Level of Total Quality Management (Global Journal of Human-Social Science, 2014)
The aim of this paper is to identify the level of Total Quality Management (TQM) in Iranian schools. Additionally, the paper aims to investigate the influence of school location and gender of principals and teachers on the level of TQM. To achieve these aims, the researchers conducted a survey research to determine the level of TQM, and used independent sample t-test to determine the significance difference between the level of TQM based on the gender of principals and teachers. They also applied one-way ANOVA and Kruskal-Wallis H test to determine the significance difference on the level of TQM based on the location of schools. The findings of this study showed that, the level of TQM is high in Iranian schools. The researchers found that there is no significant difference between TQM's level among male and female principals and teachers. It found that, there is no significant difference between the level of TQM based on the principals' schools location. But there is a significant difference between the TQM's level according to teachers' schools location. The study revealed that the level of implementation of TQM as perceived by school principals and teachers according to gender and school location. This information is useful for the provincial education authorities in shaping future TQM implementation as well as for future researches.
Keywords: total quality management; location; gender; principal; teacher; iran